Predetermined for Predestination? On the Assumed Notion of Predestination in the Dead Sea Scrolls. Issue 1 (2nd January 2019) - Justnes, Årstein
ABSTRACT: The present article argues that the concept of predestination does not on the whole lend itself to Qumran studies. Unlike the writings of Augustine and Calvin, the scrolls contain nothing like a doctrine of predestination. The article reviews several texts from 1QS, 1QH, and CD, generally understood to reflect predestination, and suggests other ways of describing and interpreting the material.